Progress of Photodynamic Therapy in Gastric Cancer. Issue 3 (1999) - Mimura, Seishiro; Narahara, Hiroyuki; Otani, Toru; Okuda, Shigeru
Abstract : Progress of photodynamic therapy (PDT) in gastric cancer and the clinical outcome are described in this paper. (1) We included the whole lesion and a 5 mm margin in the field for irradiation. Marking by injection of India-ink showing the irradiation field was performed beforehand. (2) We established the standard light dose to be 90 J/cm 2 for an argon dye laser and 60 J/cm 2 for a pulse wave laser. (3) The size of cancerous lesion curable by PDT was expanded from 3 cm in diameter, i.e. 7 cm 2 in area to 4 cm in diameter, i.e. 13 cm 2 by employing a new excimer dye laser model, which could emit 4mJ/pulse with 80 Hz pulse frequency. (4) The depth of cancer invasion which could be treated by PDT was increased from about 4 mm, i.e. the superficial part of the submucosal layer (SM-1) to more than 10 mm in depth, i.e. the proper muscular layer. These improvements owe much to the pulse laser, the photodynamic action induced by which permits deeper penetration than that of a continuous wave laser. (5) We employed a side-viewing fiberscope for gastric PDT to irradiate the lesion from an angle of 90°. (6) We designed a simple cut quartz fiber for photoradiation with a spiral spring thickened toward the end. (7) We developed an endoscopic device for photoradiation in PDT which achieves accurate and efficient irradiation. As a result of these improvements a higher cure rate was obtained even with a lower light dose of irradiation.